Role of the ferroelastic strain in the optical absorption of BiVO4 - Christina Hill; Mads C. Weber; Jannis Lehmann; Tariq Leinen; Manfred Fiebig; Jens Kreisel; Mael Guennou (APL Materials, 2020)
Bismuth vanadate (BiVO4) has recently been under focus for its potential use in photocatalysis thanks to its well-suited absorption edge in the visible light range. Here, we characterize the optical absorption of a BiVO4 single crystal as a function of temperature and polarization direction by reflectance and transmittance spectroscopy. The optical bandgap is found to be very sensitive to the temperature, and to the tetragonal-to-monoclinic ferroelastic transition at 523 K. The anisotropy, as measured by the difference in the absorption edge for the light polarized parallel and perpendicular to the principal axis, is reduced from 0.2 eV in the high-temperature tetragonal phase to 0.1 eV at ambient temperature. We show that this evolution is dominantly controlled by the ferroelastic shear strain. These findings provide a route for further optimization of bismuth vanadate-based light absorbers in photocatalytic devices.